The life-cycle of Petasiger islandicus Kostadinova & Skirnisson, 2007 (Digenea: Echinostomatidae) elucidated with the aid of molecular data - Georgieva, Simona; Kostadinova, Aneta; Skirnisson, Karl (Systematic parasitology, 2012)
The small planorbid snail Gyraulus cf. laevis (Alder) from Lake Mývatn in Iceland was found to emit large-tailed cercariae with 19 collar spines, and three-spined sticklebacks Gasterosteus aculeatus L. were infected with metacercariae of a species of Petasiger Dietz, 1909. Comparative sequence analysis using ND1 mitochondrial DNA sequences revealed that the rediae and cercariae are conspecific with P. islandicus Kostadinova & Skirnisson, 2007, recently described from an isolated population of the horned grebe Podiceps auritus (L.) at the lake. The redia, cercaria and metacercaria are described and compared with related forms.
Keywords: stadia vývoje; DNA helmintů; Phylogeny; mikroskopie; mitochondriální DNA; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; Island; DNA, Mitochondrial; Cluster Analysis; Echinostomatidae; DNA, Helminth; zvířata; Acanthaceae; sekvenční analýza DNA; fylogeneze; Smegmamorpha; shluková analýza; Iceland; Life Cycle Stages; Animals; Microscopy